DAMPAK PERUBAHAN IKLIM PANCAROBA TERHADAP PRODUKSI DAN PENDAPATAN USAHA PENGOLAHAN KERUPUK IKAN GABUS (Channa striata) DI DESA KOTA BANGUN ULU KECAMATAN KOTA BANGUN - Vanesa Hanum; Said Abdusysyahid; Muhammad Syafril (Jurnal Pembangunan Perikanan dan Agribisnis, 2017)
This study was aimed to know about the; (1) snakehead fish crackers processor’s knowledge and their responses to the climate change issues, as well as the correlation, (2) between its impact before and during the climate change to the production and income of the crackers processing, and; (3) the economic performance of the processing business before and during the climate change issue. Data collection that had been method used in this study were; Primary data, were gathered through observation and interview. And the secondary data, were gathered by the literatures interview. The sampling method that had been done was the sensus methode which all of the population as sample taken, there were eight respondents. And the data analysis that had been used were qualitative and quantitative analysis. Qualitative analyse was measured by the descriptive analysis. While quantitative analyse used non-parametric statistical analysis. The result of this study had shown; that snakehead fish crackers processors already had high knowledge and skills to response the climate change. The correlation between their knowledge and the response of the climate change were negatively strong and insignificant. The impact of the climate-change caused the decline of the both production and income the total revenue had were gathered form 2015 to 2016. They were; 348.634.258,- to Rp 67.931.581,- with RCR value 1,86 and 1,50. The actual condition of the price, sales and production above were the break-even point (BEP) for both years.